2021
DOI: 10.1080/15614263.2020.1861449
|View full text |Cite
|
Sign up to set email alerts
|

Building trust in digital policing: a scoping review of community policing apps

Abstract: Perceptions of police trustworthiness are linked to citizens' willingness to cooperate with police. Trust can be fostered by introducing accountability mechanisms, or by increasing a shared police/citizen identity, both which can be achieved digitally. Digital mechanisms can also be designed to safeguard, engage, reassure, inform, and empower diverse communities. We systematically scoped 240 existing online citizen-police and relevant third-party communication apps, to examine whether they sought to meet commu… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 37 publications
1
3
0
Order By: Relevance
“…Thus, information shared in the VSP app is highly confidential. This has supported the previous study by Elphick et al (2021) who found a significant relationship between anonymity and apps that tried to reassure users with words (such as mission statements) and apps that tried to protect users by allowing them to report things anonymously.…”
Section: Theme 2: Identity Protectionsupporting
confidence: 88%
“…Thus, information shared in the VSP app is highly confidential. This has supported the previous study by Elphick et al (2021) who found a significant relationship between anonymity and apps that tried to reassure users with words (such as mission statements) and apps that tried to protect users by allowing them to report things anonymously.…”
Section: Theme 2: Identity Protectionsupporting
confidence: 88%
“…Carter and Grommon (2015) stressed that law enforcement agencies are increasingly using mobile computing, wireless mobile broadband technology, computer and internet systems to enhance their abilities. Web Sleuthing is used to motivate citizens to get involved in police-related activities or content (Elphick et al, n.d.). Also, artificial intelligence technologies (such as cloud computing, IOTs) are used for intelligence purposes (Feldstein, 2019).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Furthermore, concern was raised about the potential of using the app as a surveillance tool, for instance, to track whether a text was received. Elphick et al (2021) have described how apps can be used to increase police trustworthiness and citizens' willingness to cooperate with police. They argued that digital technologies can help to create shared identities and online communities and allow 'digital citizens' to participate in and challenge the practices of authorities and institutions.…”
Section: Mobile Appsmentioning
confidence: 99%
“…Although not all of these considerations would apply in the current context, a number of them do. Elphick et al (2021) found that digital mechanisms:…”
Section: Mobile Appsmentioning
confidence: 99%